ESQ dan Kebutuhan Spiritualitas Civitas Akademik - Ilham Hamid (Universitas Islam Negeri Imam Bonjol Padang, 2014)
The nature of human beings are religious (homoreligious) and human nature are spiritual beings who are always working to stay in a healthy mental, in order to live happily and unseen. It has the potential of perfect spiritual intelligence to achieve